PENINGKATAN SKILL JURUSAN REKAYASA PERANGKAT LUNAK DALAM PEMBELAJARAN WEB PROGRAMMING PADA SMK NEGERI 1 SIMPANG KATIS - Wahyuningsih, Delpiah; Yuranda, Rezky; Irawan, Devi; Kirana, Chandra; Anisah (ISB Atma Luhur, 2025)
SMK Negeri 1 Simpang Katis offers a range of vocational programs, including the Software Engineering department. This community service program (PkM) was designed to enhance students’ competencies in web programming, particularly targeting final-year students. The program was implemented through a hands-on, practice-based approach using predefined case studies to guide participants through the learning process. The primary objective was to equip students with practical programming skills that would be beneficial either for entering the workforce or continuing to higher education upon graduation. As the main output of the program, participants developed a simple web-based calculator application and delivered presentations demonstrating their work. These presentations served as an evaluation tool to assess the participants’ comprehension and application of the material covered during the training.